Modeling and simulation framework for quality estimation of web applications through architecture evaluation - Blas, María Julia (2020)
The explosive growth of the cloud computing industry in recent years has paying attention to problems related to software services quality. Given that quality models serve as frameworks for quality evaluation, this paper proposes a modeling and simulation framework that measures properties derived from ISO/IEC 25010 quality model as main quality concerns of cloud computing applications. The simulation models are obtained by translating the architectural design to an equivalent functional description that, with aims to obtain the quality evaluation, explores all possible component states. Moreover, the framework automatically builds the simulation models using a set of predefined behaviors as components descriptors. Such models are combined with an experimental frame in a simulation scenario that helps to estimate quality employing the performance of the architectural design. Therefore the simulation process is hidden to software architects, providing an evaluation process able to be executed by any developer without knowledge of discrete-event simulation. Two general architectures are used as case study in order to show how works the modeling and simulation framework.